2011
DOI: 10.1186/1746-160x-7-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological profile of head and neck malignancies at University College Hospital, Ibadan, Nigeria

Abstract: IntroductionThis retrospective study analysed head and neck malignancies seen over a 19-year period at the University College Hospital, Ibadan.MethodologyOne thousand, one hundred and ninety two patients with head and neck malignancies were analysed according to age, gender, topography and histology.ResultsThere was an annual hospital frequency of 62 cases per year. The overall mean age for these malignancies was 43.9 (SD ± 19.3) years. The lesions from the respiratory tract were the most frequent (43.2%) of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
47
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(59 citation statements)
references
References 29 publications
11
47
1
Order By: Relevance
“…This is relatively low compared to studies conducted in other regions of the country. 14,16,[20][21][22][23] The male to female ratio in this study 1.2: 1. This falls within the range of 1.1 to 2.3:1 found in most studies around the country.…”
Section: Discussionmentioning
confidence: 99%
“…This is relatively low compared to studies conducted in other regions of the country. 14,16,[20][21][22][23] The male to female ratio in this study 1.2: 1. This falls within the range of 1.1 to 2.3:1 found in most studies around the country.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Malignancies in head and neck region are the tenth most common cancers in the world and are an important cause of morbidity and mortality in affected patients. 3,7 Malignant lesions can present as primary as well as secondaries from other organs.…”
Section: Introductionmentioning
confidence: 99%
“…The two most common head and neck cancers in their series were SCC, which accounted for 47.8% of cases, followed by lymphomas which accounted for 19.3% [53]. Adisa et al [27] reported that the epithelial malignancies (carcinomas) constitute 73.4% of all the cases while Lymphomas and sarcomas were 17.5% and 8.9% of cases respectively.…”
Section: Histopathological Types Of the Oral Cancersmentioning
confidence: 99%
“…In our environment, oral cancer is one of the most common lethal diseases that will be encountered in dental practice [13,20,27]. It is frequently diagnosed in late stages because most patients present to the hospital late into the course of the disease for treatment hence a poor prognosis.…”
Section: Awareness Of Oral Cancermentioning
confidence: 99%
See 1 more Smart Citation